An Expansible Aortic Ring for a Standardized and Physiological Approach of Aortic Valve Repair - Lansac, Emmanuel; Centa, Isabelle Di; Escande, Rémi; Ba, Maguette; Kellil, Nizar; Crozat, Eric Arnaud; Portocarrero, Eric; Abed, Aicha; Paolitto, Anthony; Debauchez, Mathieu; Pelle, Anne Meddahi- (IntechOpen, 2011)
None